2022
DOI: 10.3389/fcimb.2022.870785
|View full text |Cite|
|
Sign up to set email alerts
|

The Microbiota and It’s Correlation With Metabolites in the Gut of Mice With Nonalcoholic Fatty Liver Disease

Abstract: In recent years, nonalcoholic fatty liver disease (NAFLD) has become the most common liver disease in the world. As an important model animal, the characteristics of gut microbiota alteration in mice with NAFLD have been studied but the changes in metabolite abundance in NAFLD mice and how the gut microbiota affects these intestinal metabolites remain unclear. In this experiment, a mouse model for NAFLD was established by a high-fat diet. The use of 16S rDNA technology showed that while there were no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 93 publications
4
5
0
Order By: Relevance
“…Similar results were obtained in this study that Muribaculaceae had wide and negative correlations with therapeutic indicators. The abundance of Faecalibaculum is known to be significantly elevated in NAFLD mice, which was consistent with our results ( 56 , 57 ). Positive correlations were also found between Faecalibaculum and most therapeutic indicators.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were obtained in this study that Muribaculaceae had wide and negative correlations with therapeutic indicators. The abundance of Faecalibaculum is known to be significantly elevated in NAFLD mice, which was consistent with our results ( 56 , 57 ). Positive correlations were also found between Faecalibaculum and most therapeutic indicators.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with the results of human related studies, was found that in the colon, human and mice have similar bacterial species at the phylum and family level, but have differences at the genus level, which is likely caused by host species. Two studies on cecal microbiota in mice showed a significant increase in the abundance of Faecalibaculum in cecal microbiota in NAFLD mice compared with normal mice (Mu et al, 2020;Gu et al, 2022), which was similar to our results.…”
Section: Discussionsupporting
confidence: 92%
“…In NAFLD mice, at the genus level, five biomarkers in the cecum of NAFLD mice, Blautia , Desulfovibrio , Faecalibaculum , Helicobacter , and unidentified Lachnospiraceae , were also the biomarkers in the colon. Interestingly, in a previous study, Blautia , Faecalibaculum , Helicobacter and unidentified Lachnospiraceae are significantly increased in NAFLD mice ( Gu et al, 2022 ). However, the ileum and large intestine (cecum and colon) shared only a few biomarkers, with only one common biomarker at the genus level.…”
Section: Resultsmentioning
confidence: 83%
“… 26 , 27 Ileibacterium and Peptococcaceae have been reported to be positively correlated with metabolic diseases. 28 , 29 Next, at the species level, in line with our heatmap of correlation observation, the relative abundances of Lactobacillus murine, Lachnospiraceae_bacterium_MD335 and Lachnospiraceae_bacterium_A4 were increased after RA intervention compared with untreated mice. In addition, the correlation analysis suggested that murine Lactobacillus was involved in inhibiting XOD activity in serum and improving liver and kidney functions.…”
Section: Discussionsupporting
confidence: 65%